Tinjauan Yuridis Terhadap Transparansi dan Akuntabilitas Pengelolaan Keuangan Negara di Era Digital - Basri, Hasan; Rohim, Abdur (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The digital era has brought significant changes in state financial management, particularly in terms of transparency and accountability. This study aims to juridically examine how the principles of transparency and accountability are applied in state financial management in the digital era and to evaluate the effectiveness of existing regulations. The research employs a normative approach using literature review (library research), analyzing various laws, legal documents, and previous studies relevant to the topic. The findings indicate that digitalization in state financial management, such as the implementation of e-budgeting and e-audit systems, has improved public access to financial information and accelerated the oversight process. However, challenges remain in its implementation, including legal gaps in data protection, risks of digital manipulation, and a lack of technical expertise in certain state financial management institutions. Additionally, while regulations on transparency and accountability have been strengthened, their effectiveness still largely depends on the consistency of law enforcement and political commitment. Therefore, policy reforms that are more adaptive to technological developments and the strengthening of more responsive oversight mechanisms are needed. This study is expected to contribute to the development of better legal policies to ensure state financial management that is more transparent, accountable, and free from misuse in the digital era.